Reviving the inter-laboratory comparison measurement results. (February 2020) - Arif Sanjid, Mahammed; Ghoshal, Sanjoy K; Sen, Mrinal
Key comparison measurements serve as an ultimate tool of quality assurance of results. Whenever the inter-comparison results indicate inconsistency, the participating laboratory needs to take the corrective actions. Practically, the systematic errors involved in the measuring system confines the achievable accuracy. Therefore, the corrective action involves either empirically determine the influences afresh or intuitively reassigns these error values. Alternatively, an analytical method based on inter laboratory comparison results is proposed. The novelty of the proposal is considering task-specific errors in the model that is used for the analysis of interlaboratory comparison results. Without accounting the uncertainties of task-specific errors, the analysis grows complicated and even sometimes it is not feasible. To supplement the proposed method, task-specific errors due to the imperfect geometry of ring gauge, practical inability in implementing the measurement, and unattended environmental influences are explored. The proposed method is demonstrated using some internal diameter key comparison data. The systematic errors responsible for the outlier in the measurement comparison are clearly distinguished.